2021
DOI: 10.3389/fimmu.2021.656362
|View full text |Cite
|
Sign up to set email alerts
|

How to Manage COVID-19 Vaccination in Immune-Mediated Inflammatory Diseases: An Expert Opinion by IMIDs Study Group

Abstract: Since March 2020, the outbreak of Sars-CoV-2 pandemic has changed medical practice and daily routine around the world. Huge efforts from pharmacological industries have led to the development of COVID-19 vaccines. In particular two mRNA vaccines, namely the BNT162b2 (Pfizer-BioNTech) and the mRNA-1273 (Moderna), and a viral-vectored vaccine, i.e. ChAdOx1 nCoV-19 (AstraZeneca), have recently been approved in Europe. Clinical trials on these vaccines have been published on the general population showing a high e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 120 publications
(136 reference statements)
0
35
1
3
Order By: Relevance
“…A recent opinion paper on COVID-19 vaccination in immune-mediated diseases concluded that ocular (immune-mediated) side effects were very unlikely to happen, which should, however, not prevent us to be vigilant [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent opinion paper on COVID-19 vaccination in immune-mediated diseases concluded that ocular (immune-mediated) side effects were very unlikely to happen, which should, however, not prevent us to be vigilant [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…В целом отсутствие синтеза нейтрализующих антител имело место у каждого 10-го пациента (9,5%), o n l i n e fi r s t Таблица 3. Рекомендации по терапии и вакцинации пациентов с ревматическими заболеваниями в период пандемии COVID-19 [90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108] Продолжение таблицы 3 o n l i n e fi r s t страдающего ИВРЗ, и у каждого 100-го (0,5%) в группе контроля. Наконец совсем недавно было показано, что базовое лечение МТ ассоциируется с неадекватным синтезом анти-SARS-CoV-2 (у 62,2% пациентов) и отсутствием вирусспецифической активации CD8 + -Т-клеток [169].…”
Section: Discussionunclassified
“…The best criterion, therefore, to evaluate the priority level of access to COVID-19 vaccine in these patients is the clinical one [ 124 ]: in patients with AIAIDs under heavy immunosuppressive therapy and a history of serious and recurrent infections, the immunology specialist will determine the priority level, in keeping with the Raccomandazioni ad interim sui gruppi target della vaccinazione anti-SARS-CoV-2/COVID-19 (GURI 24.3.2021), elaborated by the Italian Ministry of Health. It is necessary to emphasize that vulnerable patients with markedly dysfunctional immune systems may act as an incubator for SARS-CoV-2 variants.…”
Section: Should Patients With Aiaids Pids and Sids Be Prioritized In The Access To Vaccines?mentioning
confidence: 99%
“…There is no general agreement regarding priority criteria for anti-COVID vaccine access for patients with AIAIDs, PIDs, and SIDs, because there is no consensus on their actual risk of infection or developing a more serious disease. The best criterion to evaluate the priority level of access to COVID-19 vaccine in these patients is the clinical one [ 124 ]: in patients with AIAIDs under heavy immunosuppressive therapy and a history of serious and recurrent infections, the immunology specialist should determine the priority level, in keeping with the Raccomandazioni ad interim sui gruppi target della vaccinazione anti-SARS-CoV-2/COVID-19 (GURI 24.3.2021), elaborated by the Italian Ministry of Health. Clinical criteria should guide the management of patients with PIDs and SIDs as well.…”
Section: Recommendationsmentioning
confidence: 99%